The Effect of Marijuana Legalization on Anticipated Use: A Test of Deterrence Theory - Arazan, Christine; Costelloe, Michael; Hall, Tricia M. (International Journal of Criminology and Sociology, 2015)
Marijuana is the most frequently used illicit drug in the world (Erickson, Van Der Maas, and Hathaway, 2013:428). Here in the United States, public support for the legalization of marijuana for recreational use is substantial. With public support, both Colorado and Washington passed state initiatives in 2012 to legalize recreational use of marijuana for individuals aged 21 years and older. Even the federal government has recently reversed their initial position to continue to enforce federal drug laws within these states. With what appears to be increasingly liberal attitudes toward marijuana use and even toward legalization, some are concerned about what this may mean for drug use in America. To many, it appears obvious that with changing attitudes and more lenient policies, use of marijuana will increase and in turn exacerbate a host of individual and societal problems that marijuana use is thought to cause. The primary focus of this study examines the first part of these concerns: to what extent will marijuana use increase with these policy changes? Specifically, this research looks at what extent current abstainers of marijuana might use if it were legalized.